Evaluation of O-Cresol removal using Pva-Cryogel-Immobilised biomass enhanced by pac - See, S.; Lim, P.E.; Lim, J.W.; Seng, C.E.; Adnan, R. (African Water Research Commission, 2015)
Evaluation of o-cresol removal using PVA-cryogel-immobilised biomass enhanced by PAC S See, P Lim, J Lim, C Seng, R Adnan